PENGARUH SAINS DALAM PERKEMBANGAN MODERN MENURUT MUHAMMAD ABDUH - Ahmad Nabil Amir; Tasnim Abdul Rahman (MAHABBAH : Jurnal Ilmu Ushuluddin Dan Pemikiran Islam, 2025)
This article examines the scientific thought of Shaykh Muhammad Abduh (1849-1905) ideas on science by systematically analyzing his extensive works on science, such as Al-Islam wa al-Nasraniyyah Ma‘a al-‘Ilm wa’l-Madaniyyah (Islam and Christianity in Relation to Science and Civilization), Tafsir al-Manar (The Manar Commentary), Tafsir Juz ‘Amma (the Commentary of Juz ‘Amma), Risalat al-Tawhid (Treatise on the Unity of God), Journal al-Manar (the Lighthouse) and other important literary works and prolific writings of Muhammad ‘Abduh. The principal themes discussed in this work concentrated on Muhammad Abduh’s philosophy of science, ‘Abduh’s contributions to modernity, and his scientific views in the Qur’an. It also discussed his influence on the modern Egypt and its important impact in the enlightening and reforming of modern Islam. The method of study is qualitative (narrative) in nature based on literature survey. The study significantly arrived at considerable result which demonstrates that Abduh’s primary contribution to science and technology is to Islamize its dynamic character and foundation based on modern Islamic worldview. This was significantly illustrated in his endeavor to present scientific commentary of the Qur’an which focused on the primacy of ‘aql (intellect) and reason, unleashing his rational understanding of the text, and contributing to the revival of scientific thought, the freedom of ideas (taharrur) and dynamic religious worldview.